أهمية استقامة أصحاب الطرق الصوفية ووحدة المسلمين في نيجيريا - Muhammad Yusuf Khalid; Abdullah Orakiuyo Hanafi (Universiti Sains Islam Malaysia, 2024)
This study examines one of the reasons associated with the difference and disunity among Muslims in Nigeria. It is the mischievous acts of some spiritual leaders of various Sufi orders. This paper aims at setting Sufism free of their misrepresentation and at the same time inviting Sunnis to reconsider their stand on Sufism as an innovation. Qualitative Method was used together with the personal experience of the researchers. The findings show that mysticism is an integral part of Islam, and that its Islamic cultural origin is more affirmed than its innovation. It has also been confirmed that various spiritual malpractices in the name of Sufism are rampant in the Sufi orders in Nigeria; and without erasing them, the dream of unification among Nigerian Muslims may not come to pass. Keywords: Integrity, Sufi orders, Muslim unity